Zmiana preferencji wyborczych w Szwecji w wyniku kryzysu migracyjnego - Kobierecka, Anna (Historia i Polityka, 2019)
The migration crisis influenced the internal situation in Sweden to a great extent. Owing to an intensive migrant inflow and a massive submission of asylum applications, the topic of immigration became an integral part of the political discourse. Therefore, a question should be asked, whether intensified migration will cause any visible changes in Sweden, especially in the field of politics and social attitudes towards foreigners. Sweden, until now, has been perceived as a tolerant and open state and society. The aim of the article is to test the hypothesis assuming that there is a correlation between the migration crisis, the radicalisation of the Swedish society and the growing support for the Sweden Democrats, the only anti-immigration political party in Sweden.